Digital activism decoded : the new mechanics of change - Joyce, Mary (Mary C.) (International Debate Education Association, 2010)
"The media has recently been abuzz with cases of citizens around the world using digital technologies to push for social and political change: from the use of Twitter to amplify protests in Iran and Moldova to the thousands of American non-profits creating Facebook accounts in the hopes of luring supporters. These stories have been published, discussed, extolled, and derided, but have not yet been viewed holistically as a new field of human endeavor. We call this field "digital activism" and its dynamics, practices, misconceptions, and possible futures are presented together for the first time in this book."--Pub. desc